DETECTION OF EMERGENCE OF MAGNETIC FLUX TUBES IN THE PHOTOSPHERES OF DWARF 61 Cyg A, SUBGIANT β Aql AND GIANT β Gem - Plachinda, S I.; Butkovskaya, V. V. (Одеські астрономічні публікації, 2020)
Today, the study of stellar magnetic fi- elds is one of the important research field in astrophysi- cs because it provides us, in addition to physics, with information about space weather in the orbits of Earth- like planets in stars other than the Sun. Local magnetic fields on stars with convective envelopes are small-scale magnetic fields different in nature and structure from their global magnetic field. Unlike the Sun, through direct measurements we are able to measure only the magnetic field integrated over the visible disk of stars. However, we can register the magnetic field in the leading spot during the time interval when the corresponding magnetic flux tube already emerges on the surface of the star, and the magnetic flux tube of the following spot is still hidden in the interior under the photosphere. Our research is based on the spectropolarimetric observations carried out with 2.6m Shajn telescope equipped with the echelle spectrograph ESPL, CCD, and the Stokesmeter as a circular polari- zation analyzer. For measuring stellar magnetic fields the Single Line (SL) technique was developed at CrAO. This technique is based on the calculation of Zeeman effect in individual spectral lines. A key advantage of the SL technique is its ability to detect local magnetic fields on the surface of stars. Using SL technique emergence of large magnetic flux tubes at the surface of stars of V-IV-III luminosity classes (61 Cyg A, β Aql, β Gem) were first registered. We review the results of the study of local magnetic fields in these stars, includi- ng the results of modeling of magnetic field flux density and the size of their starspots. We also present the new results of spots modeling on β Aql. According to the considered geometric model, the rotational variabili- ty of the magnetic field and the extreme value of the field obtained from observations, we assume that the extreme radius of the spots at the surface of β Aql may exceed 9 ◦ .